Point‐of‐care ultrasound in the COVID‐19 era: A scoping review. Issue 2 (17th December 2020) - Yau, Olivia; Gin, Ken; Luong, Christina; Jue, John; Abolmaesumi, Purang; Tsang, Michael; Nair, Parvathy; Tsang, Teresa S. M.
Abstract: In the midst of the COVID‐19 pandemic, unprecedented pressure has been added to healthcare systems around the globe. Imaging is a crucial component in the management of COVID‐19 patients. Point‐of‐care ultrasound (POCUS) such as hand‐carried ultrasound emerges in the COVID‐19 era as a tool that can simplify the imaging process of COVID‐19 patients, and potentially reduce the strain on healthcare providers and healthcare resources. The preliminary evidence available suggests an increasing role of POCUS in diagnosing, monitoring, and risk‐stratifying COVID‐19 patients. This scoping review aims to delineate the challenges in imaging COVID‐19 patients, discuss the cardiopulmonary complications of COVID‐19 and their respective sonographic findings, and summarize the current data and recommendations available. There is currently a critical gap in knowledge in the role of POCUS in the COVID‐19 era. Nonetheless, it is crucial to summarize the current preliminary data available in order to help fill this gap in knowledge for future studies.